THE DISPARITY IN NATIONAL EMISSIONS: THE ROLE OF NATIONAL POLICY TO MITIGATE CLIMATE CHANGE FREE RIDER - Bram, Deni (Indonesian Journal of International Law, 2013)
It is generally accepted within the scholarly international community that global climate change is occurring and is due at least in part to anthropogenic activity. Strategies to mitigate climate change harms and adapts to inevitable climate change-induced consequences are influencing legal, political, and human rights frameworks. One of the interesting study is the study to test the existences of justice aspect in the regulation for international as well as for national nowadays in overcome the climate change problem. The research focuses on some main points, which consist of several problems. First, to perform assessments about the importance of climate justice contexts in the spirit of climate change prevention; Secondly, to search for the basic understanding for the interests of developing countries to be treated equitably in the climate change regime; Lastly, to search for factual condition on free rider from the emissions quota that Indonesia received in International climate change system.